IMPLEMENTATION OF INDEPENDENT CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION AND CHARACTER SUBJECTS AT NAHDLATUL ULAMA 2 GRESIK JUNIOR HIGH SCHOOL - Yaqin, Pais Ainul; Abdullah, Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The implementation of the Independent Curriculum as a response to education in Indonesia after the COVID-19 pandemic, considering that many students have experienced learning delays. Focusing on overcoming learning loss and learning crisis is a strategic step to help students return to their education process; the Independent Curriculum is one solution to overcome problems in the world of education. This study aims to determine 1) How is the implementation of the independent curriculum in the subjects of Islamic Religious Education and Character Education at SMP Nahdlatul Ulama 2 Gresik, 2) What are the problems of implementing the independent curriculum in the subjects of Islamic Religious Education and Character Education at SMP Nahdlatul Ulama 2 Gresik, and 3) What are the efforts to overcome the problems of implementing the independent curriculum in the subjects of Islamic Religious Education and Character Education at SMP Nahdlatul Ulama 2 Gresik. This study is a descriptive qualitative approach that takes SMP Nahdlatul Ulama 2 Gresik as the object through data collection through interviews, observation, and documentation. The informants in this study were the principal, the vice principal of curriculum, the Islamic Religious Education and Character Education teacher, and grade VII students. The study results showed that 1) The implementation of the Independent Curriculum, which includes training, the creation of teaching modules, and P5 activities outside of school hours, shows the school's commitment to creating a better learning experience for students. 2) The implementation of the problem-based learning method and clear steps in learning activities show that teachers have understood and implemented the principles of the Independent Curriculum well. 3) The advantages and disadvantages of implementing the Independent Curriculum are widespread, especially during the transition from traditional teaching methods to more modern approaches—the existing advantages, such as fun and varied learning. Additional training or collaboration between teachers to share best practices may be possible to overcome shortcomings, such as the use of lecture methods and understanding of diagnostic assessments.